A look at the Solidarity Organizations active in the Province of Guanentá Department of Santander Colombia - Corzo Gutiérrez, Nohora; Sarmiento Blanco, Uriel; Fajardo, Miguel Arturo (Cooperativismo & Desarrollo, 2020)
The solidarity economy has evolved for more than 40 years, to such an extent that some researchers see the southern provinces of Santander as a setting for the Cooperative Model, a great development alternative for the regions. Therefore, the general objective of this study was the characterization of the Solidarity Organizations (OS) active in the province of Guanentá. In the first place, the existing solidarity organizations were identified, subsequently, a mapping of said entities was carried out and, finally, some significant solidarity experiences present in the region were identified. For the research, a mixed approach (quantitative and qualitative), descriptive-exploratory and cross-sectional, was used as a methodology. The techniques used were the survey and the interview, the instrument used was the questionnaire. It is worth mentioning that the survey was applied to 399 OSs and the interview to 11 OSs identified as significant experiences. The findings found will serve as a source of information for institutions interested in strengthening the development of the solidarity economy in the municipalities. Likewise, the article highlights the characteristics of the social capital of solidarity organizations, especially their commitment and action in social transformation.